The Clinical Outcomes of Surgical Treatment of Noncontiguous Spinal Tuberculosis: A Retrospective Study in 23 Cases - Huang, Jia (Public Library of Science, 2014)
STUDY DESIGN: A retrospective clinical study. OBJECTIVE: To evaluate the clinical efficacy of the surgical treatment of noncontiguous spinal tuberculosis (NSTB), and to discuss its therapeutic strategies. METHODS: We performed a retrospective review of clinical and radiographic data that were prospectively collected on 550 consecutive spinal tubercular patients including 27 patients who were diagnosed and treated as NSTB in our institution from June 2005 to June 2011. Apart from 4 patients being treated conservatively, the remainder received surgery by posterior transforaminal debridement, interbody fusion with instrumentation, posterior instrumentation and anterior debridement with fusion in a single or two-stage operation. The clinical outcomes were evaluated before and after treatment in terms of hematologic and radiographic examinations, bone fusion and neurologic status. The Oswestry Disability Index score was determined before treatment and at the last follow-up visit. RESULTS: 23 patients (15 M/8F), averaged 44.6±14.2 years old (range, 19 to 70 yd), who received surgical treatment, were followed up after surgery for a mean of 52.5±19.5 months (range, 24 to 72 months). The kyphotic angle was changed significantly between pre- and postoperation (P<0.05). The mean amount of correction was 12.6±7.2 degrees, with a small loss of correction at last follow-up. All patients achieved solid bone fusion. No patients with neurological deficit deteriorated postoperatively. Neither mortalities nor any major complications were found. There was a significant difference of Oswestry Disability Index scores between preoperation and the final follow-up. CONCLUSION: The outcomes of follow-up showed that posterior and posterior-anterior surgical treatment methods were both viable surgical options for NSTB. Posterior transforaminal debridement, interbody fusion and posterior instrumentation, as a less invasive technique, was feasible and effective to treat specific tubercular foci.